Clinical Characteristics and Prognosis of Adult Orbital Cellulitis in a Tertiary General Hospital - Bangtao Yao; Yuhua Ding; Xiaogui Zhao; Bei Wang; Gang Liu; Fei Wang (Journal of Ophthalmology)
Purpose. Adult orbital cellulitis (OC) occurs relatively rarely, and comprehensive studies that retrospectively evaluate OC are lacking. Here, we aimed to examine the clinical characteristics and prognosis of OC in a tertiary general hospital. Methods. Between October 2010 and May 2019, patients presenting with clinical symptoms of OC in a tertiary general hospital were analyzed in this retrospective study. Twenty-six cases were identified for a detailed review. In these cases, 16 males and 10 females were diagnosed with orbital cellulitis by clinical characteristics and multimodal examinations. We divided patients into three groups: (1) patients secondary to rhinosinusitis, (2) patients secondary to endogenous infection(s) without endophthalmitis, and (3) patients secondary to endophthalmitis. For each group, age, gender, eye type, combined systemic diseases, clinical presentation, leukocyte count, blood culture, diagnostic imaging, therapeutic methods, length of stay, time of postoperation, and patient prognosis were analyzed in detail. Results. There were no significant differences regarding age, gender, preoperative leukocyte count, exophthalmia, blood culture, treatment, or visual changes within the three groups (P<0.05). There were significant differences, however, in postoperative leukocyte count and ophthalmoplegia between the three groups (P<0.05). The preoperative and postoperative logarithms of the minimum resolution angle scored by the best-corrected visual acuity (LogMAR BCVA) of group 3 were statistically significant compared to group 1 and group 2 (P<0.05). Conclusion. We confirmed that the prognosis of OC patients combined with systemic diseases was poor. Patients with OC secondary to endophthalmitis infrequently experience ophthalmoplegia; however, these patients still have poor visual outcomes. Patients cultured positive for Klebsiella pneumoniae infection may not be associated with liver abscess. The level of leukocytes may indicate the condition of the disease.